ANALISIS NILAI PENDIDIKAN AKHLAK DAN RELEVANSI DENGAN PENDIDIKAN KARAKTER DALAM NOVEL “NEGERI 5 MENARA” KARYA AHMAD - Muhammad Lutfillah; Muhammad Hanif; Muhammad Afifulloh (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The development of culture is now much more rapid, several steps ahead of the previous era, where human communication methods are still far from feasible. The development of the times also affects the development of the realm of literary development. Many literary works have sprung up in society. Especially Novels. There are many novels that contain values that can be taken by the reader. An example is the novel by Ahmad Fuadi which has the title Negeri 5 Menara. This novel tells about the concept of education which has a background in a modern Islamic boarding school.The novel has educational values that can be used as a reference. One of them is about the value of moral education. Moral education is an very important element in the world of education. Therefore, humans need not only knowledge, but also need spiritual strength that can shape character as a complete human being (insan kamil) in accordance with the norms in Islam.